Free posterior tibial artery perforator flap for 2‐stage tracheal reconstruction in patients after resection of well‐differentiated thyroid carcinoma invading the trachea. Issue 7 (6th February 2019) - Liu, Jun; Lu, Dan; Deng, Di; Wang, Ji; Gan, Weigang; Zou, Jian; Chen, Fei; Yang, Hui
Abstract: Background: The present study was conducted to explore the efficacy of using a free posterior tibial artery perforator flap (FPTAPF) for trachea reconstruction after resection of well‐differentiated thyroid carcinoma (WDTC) invading the trachea. Methods: We retrospectively collected and analyzed clinical and surgical data from 14 patients who underwent tracheal reconstruction using a FPTAPF after resection of WDTC invading the trachea between August 2014 and July 2017. Results: Satisfactory tracheal structure and functional recovery were obtained in 11 of the 14 patients. One patient had breathing difficulties after tracheostomy closure tests because of bilateral recurrent laryngeal nerve damage caused by disease invasion. Tracheostomy incision was not closed in 2 patients because they received postoperative adjuvant radioactive iodine 131 treatment. Conclusion: Satisfactory tracheal reconstruction results were achieved in patients with resection of WDTC invading the trachea, indicating that a FPTAPF is a safe and reliable choice for management.